2001
DOI: 10.1117/12.425261
|View full text |Cite
|
Sign up to set email alerts
|

<title>Recent advances in endpoint and in-line monitoring techniques for chemical-mechanical polishing processes</title>

Abstract: Executive SummaryWe present a summary of the recent advances in endpoint and in-line monitoring techniques for chemical-mechanical polishing (CMP) processes. We discuss the technical challenges and review some of the approaches that have been published and/or patented. These methods include optical, thermal (pad temperature), friction (torque motor current), electrochemical, chemical, electrical, and acoustic (vibration). We also present experimental data obtained in our laboratory using selected endpoint meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The most popular of such methods measures the carrier or the platen motor current (CMC or PMC). [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] During polishings, both wafer and platen rotate at desired velocity setpoints. The pad-slurry-wafer interface undergoes a myriad of 3-body interactions which, due to the frictional forces involved, may facilitate or resist the platen and wafer rotation.…”
mentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The most popular of such methods measures the carrier or the platen motor current (CMC or PMC). [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] During polishings, both wafer and platen rotate at desired velocity setpoints. The pad-slurry-wafer interface undergoes a myriad of 3-body interactions which, due to the frictional forces involved, may facilitate or resist the platen and wafer rotation.…”
mentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37][38][39] The most popular of such alternate methods is centered around measuring the carrier, or the platen, motor current (CMC, or PMC). [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] During CMP, the wafer and the platen co-rotate at desired velocity setpoints. The pad-slurry-wafer interface undergoes a myriad of 3-body interactions which, due to the frictional forces involved, may facilitate or resist platen and wafer rotation.…”
mentioning
confidence: 99%
“…Carrier head motor current measurements, sometimes combined with the Hall Effect, correspond to instantaneous changes in friction at the interface. 6 Another method relies on a displacement sensor attached to the shaft that rotates the wafer carrier. One study found a principal vibration mode of their polisher, and that the RR of oxide correlated to shear force intensity without significant change in COF.…”
mentioning
confidence: 99%